An overview of bond behavior of recycled coarse aggregate concrete with steel bar - Su Tian (De Gruyter, 2021)
In this paper, an overview focusing on the bond behavior of recycled coarse aggregate concrete (RAC) with steel bar is carried out. The results show that the failure modes of RAC specimen were not only influenced by a single factor, it is necessary to comprehensively consider the influence of various factors on the failure modes of RAC specimen; The steel bar diameter, the concrete cover to diameter ratio and the replacement rate of RCA all affect the load-slip curve of RAC specimen; Bond strength predictive equations and bond-slip relationship models of RAC with steel bar has been summarized to ensure engineers to better understand their applicability; The influencing factors of the bond behavior of RAC specimens including the replacement rate of RCA, the concrete compressive strength, the steel bar type and steel bar diameter, the steel bar embedment length and the aggregate performance; The freeze-thaw cycles and the steel bar corrosion all affect the bond behavior of RAC with steel bar. When freeze-thaw damage and steel bars corrosion reach a certain degree, the bond behavior of RAC with steel bar deteriorates.